Affixes Analysis in “The Parable of the Lost Sheep Story” to English Young -Learners: A Morphological Perspective - Lumoindong. B; Oatman. G. A (Tamilis Synex: Multidimensional Collaboration, 2024)
The aims of this research were to know the kinds of affixes and how they were used in “the parable of the lost sheep story”. Affix is a part of morphology. Morphology is the study of the internal structure of word. There are two kinds of morphology, which are derivational and inflectional. Both derivational and inflectional morphologies are related to affixes. Affixes can be distinguished by two primary types, they are: prefixes and suffixes. Prefixes are attached at the beginning of a lexical item or base morpheme, while suffixes are attached at the end of a lexical item or base morpheme. Derivational affixes caused the semantic changes, while inflectional affixes result in no changes. Affixes are commonly used in many sentences to construct a story. Descriptive qualitative was used as the method to do this research. The results of this research showed that there are 6 suffixes found in the story, they are -es, -s, -ing, -ed, -ly and -th, and two prefixes, they are re- and step-.